Consumer anxieties about food grain safety in China. (March 2017) - Zhu, Huying; Jackson, Peter; Wang, Wentao
Abstract: China has a long history of eating staple plant foods which are mainly derived from food grains, especially rice and wheat. Food grain safety has been a worrying challenge on health and nutrition grounds in China, although evidence clearly suggests that expanding agricultural production is linked to reducing undernourishment. The focus of this study is to investigate consumers' anxieties about food grain safety in China. The nature and extent of consumer anxieties about grain safety, the cause of these anxieties, and possible ways to relieve anxiety are empirically analyzed. Data were collected using semi-structured interviews with 142 grain consumers in 29 provinces of China, in both rural and urban areas, during 2016. The results show that consumers are worried about the production and processing safety of food grains and genetically modified cereals and that the causes of anxiety are varied. Anxiety is amplified by social media reports of food scandals, polluted ecological environments, the high incidence of food-related chronic diseases and cancer, concerns about food system governance and lack of knowledge and ability to identify grain quality. Consumers seek to relieve their anxiety by identifying grain quality themselves, choosing foreign grains and paying close attention to reports about unsafe food. These findings have important implications for future programs aimed at improving consumer confidence about grain safety. Highlights: This paper explores food grain safety from a consumer perspective in China. The paper shows that consumer anxieties are a social phenomenon. Data were collected using semi-structured interviews with consumers. The paper outlines the nature of consumer anxieties about grain safety.